The Argentinean oil policy of the Frondizi’s government (1958:1962): An analysis from the accumulation by dispossession’s theory - Gómez-Lende, Sebastián (2022)
Rivers of ink have flowed in order to explain why the Argentinean company YPF -the first vertically integrated state oil company of the capitalist world- entered the long phase of decline that led to ist privatization during the neoliberal decade of 1990s. Nevertheless, scarce research has focused on the primary origin of such process: the oil policy carried out during the developmentalist government of Arturo Frondizi (1958-1962). According to that argument, this paper analyzes the hydrocarbon policy of such president in light of the categories proposed by the accumulation by dispossession’s theory. The findings show the ocurrence of various phenomena, such as the purchase of political influence by the corporations, the aprobations of laws to protect and favour their interests, the signing of public works contracts with inflated costs, the semi-privatization of petroleum areas, the neocolonial, imperial appropriation of natural resources, and the granting of explicit profit garantees through “political prices”, economic subsidies, trade and tax exemptions, and other leonine conditions to the oil capital, all of them in a framework at odds with legality and institucional transparence. It is concluded that the Frondizi’s oil legacy configured the beggining of the end for YPF, since it laid the foundation for both the future relationship between state and oil capital and the accumulative looting that, thirty years later, would go the bankrupt and the privatization of the company.